New Pharmacological Strategies for the Treatment of Non-Infectious Uveitis. A Minireview - Rodrigo A. Valenzuela; Rodrigo A. Valenzuela; Iván Flores; Beatriz Urrutia; Francisca Fuentes; Pablo E. Sabat; Pablo E. Sabat; Carolina Llanos; Loreto Cuitino; Loreto Cuitino; Cristhian A. Urzua; Cristhian A. Urzua; et al. (Frontiers Media S.A., 2020)
Non-infectious uveitis (NIU) is a group of disorders characterized by intraocular inflammation at different levels of the eye. NIU is a leading cause of irreversible blindness in working-age population in the developed world. The goal of uveitis treatment is to control inflammation, prevent recurrences, and preserve vision, as well as minimize the adverse effects of medications. Currently, the standard of care for NIU includes the administration of corticosteroids (CS) as first-line agents, but in some cases a more aggressive therapy is required. This includes synthetic immunosuppressants, such as antimetabolites (methotrexate, mycophenolate mofetil, and azathioprine), calcineurinic inhibitors (cyclosporine, tacrolimus), and alkylating agents (cyclophosphamide, chlorambucil). In those patients who become intolerant or refractory to CS and conventional immunosuppressive treatment, biologic agents have arisen as an effective therapy. Among the most evaluated treatments, TNF-α inhibitors, IL blockers, and anti-CD20 therapy have emerged. In this regard, anti-TNF agents (infliximab and adalimumab) have shown the strongest results in terms of favorable outcomes. In this review, we discuss latest evidence concerning to the effectiveness of biologic therapy, and present new therapeutic approaches directed against immune components as potential novel therapies for NIU.